2007
DOI: 10.3144/expresspolymlett.2007.36
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of the reactivation process in the adhesion of chlorinated SBS rubber with polychloroprene adhesives

Abstract: Abstract. Chlorination treatment of a thermoplastic styrene-butadiene-styrene rubber (SBS) with a 3 wt% solution of trichloroisocyanuric acid (TCI) in methyl ethyl ketone (MEK) introduces chlorinated and oxidized moieties on the rubber surface which increase its surface energy and produces surface microroughness. Consequently adhesion properties, evaluated by T-peel strength measurements in chlorinated SBS/solvent based-polyurethane adhesive/leather joints, are enhanced. In this study, two solvent-based polych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…27,56,[57][58][59][60]63 Paiva et al 55 concluded that to maximize peel strength of the single lap joints leather/TR and leather/PUR joints, it is necessary to apply some surface treatments: on TR -chemical treatment, on leathermechanical treatment and primer and on PU -mechanical treatment and primer. Navarro-Ban˜o´n et al 64 concluded that chemical treatment as surface treatment increases the SBS rubber surface energy and introduced surface roughness, improving the adhesion with PU and PCP adhesive types in upper-to-sole joints. Each material requires the application of a specific surface treatment, as shown in Table 11.…”
Section: Surface Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…27,56,[57][58][59][60]63 Paiva et al 55 concluded that to maximize peel strength of the single lap joints leather/TR and leather/PUR joints, it is necessary to apply some surface treatments: on TR -chemical treatment, on leathermechanical treatment and primer and on PU -mechanical treatment and primer. Navarro-Ban˜o´n et al 64 concluded that chemical treatment as surface treatment increases the SBS rubber surface energy and introduced surface roughness, improving the adhesion with PU and PCP adhesive types in upper-to-sole joints. Each material requires the application of a specific surface treatment, as shown in Table 11.…”
Section: Surface Treatmentsmentioning
confidence: 99%
“…Paiva et al 55,63 concluded that applying solventbased PU adhesive to bond PU soles to leather upper, the peel strength is capable to satisfy the minimum requirements for the footwear industry, since applied the correct surface treatment. Navarro-Ban˜o´no et al 64 concluded that is possible to obtain good results of peel strength using PU and PCP adhesive types to manufacture SBS/adhesive/leather joints; however, to eliminate the reactivation process with PCP adhesive, it is necessary to use thermoreactive phenolic resin on the formulation.…”
Section: Peel Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Styrene-butadiene copolymers (SBC) have a wide field of applications as shoe soles, impact modifiers, asphalt modifiers, adhesives and sealants. Several kinds of SBC have been used in adhesive formulations and as films in adhesives [2,6,7]; however, study of radial structure is not reported before.…”
Section: Adhesive Formulationsmentioning
confidence: 99%
“…Cumiloxy radical can experiment beta cleavage to form acetophenone and methyl radical (figure 1). Some reports have use IR for evaluation of grafting surface and evaluation of curing reaction in adhesives reporting that is a useful tool for that kind of studies [12,13]. Also is possible with IR to identify decreasing of peaks attributed to double bonding in polybutadiene backbone when crosslinking process is carry out [14].In this case, radical energy does not reduce significatively, then peroxide eficiency is not alterated, with advantage that methyl radical is not esterically hindranced as initial cumiloxy radical and can participate more effectively in reactions where esteric limitations or diffusion are a limitation.…”
Section: • Must Have a Partially Elastic Behaviormentioning
confidence: 99%